An agent-based approach for information and knowledge sharing in manufacturing enterprise networks. (7th September 2004) - Shen, Weiming; Norrie, Douglas H.
Market globalisation and frequently changing customer requirements are forcing manufacturing enterprises to reconsider how they are organised. On the other hand, companies feel the need to focus their core competencies and are downloading product development tasks to their suppliers. As a result, related manufacturing enterprises are closely joined together through, e.g., virtual enterprises, using advanced information and communication technologies. Sharing and exchange of information and knowledge among related enterprises becomes more and more important. This paper presents our agent-based approach to organise enterprise's activities and those of its customers, suppliers and partners into an open dynamic environment via networks to facilitate the sharing and exchange of information and knowledge related to customer requirements, products, production, and services, etc. A hybrid agent-based architecture is proposed, main features of this architecture are described and a prototype implementation is presented.